Multiscale analysis and experimental validation of crack initiation in quasi-isotropic laminates. (1st June 2020) - Kumagai, Yuta; Onodera, Sota; Salviato, Marco; Okabe, Tomonaga
Abstract: A multiscale approach comprising laminate-scale finite-element (FE) analysis and fiber-diameter-scale periodic unit cell (PUC) analysis was developed to predict matrix microcracking in quasi-isotropic laminates; further, this method was validated through comparison of our predictions with experimental results. In the mesoscopic FE analysis, the nonlinear deformation in the unidirectional laminae was incorporated to reproduce the deformation behavior of the laminate and obtain deformation histories at the locations of expected crack initiation in the laminate. In the microscopic analysis, the nonlinear behavior and crack initiation in the matrix resin were simply modeled by an elasto-viscoplastic law and a stress-based failure criterion, respectively. To predict crack initiation considering both the macroscopic deformation fields and the microscopic heterogeneity of the material, the mesoscopic FE analysis was conducted first. Subsequently, the microscopic PUC analysis was undertaken based on the strain histories obtained from the mesoscopic analysis. Our multiscale approach was applied to quasi-isotropic laminates with several laminate configurations to predict the matrix cracks in the 90 ∘ ply of the laminates. In addition to referring to experimental data cited in literature, initial and transverse cracks were observed when conducting tensile tests of quasi-isotropic laminates using the in situ replication technique and ex situ X-ray computed tomography. Through comparison of the predicted values with experimental results quoted in literature and obtained in this work, we validated the prediction capability of our multiscale analysis and evaluated the process of crack formation from the mesoscopic and microscopic points of view. Moreover, we examined the sensitivity of the predicted results to fiber arrangement and the influence of constitutive and failure modeling of the two-scale analysis on the predicted cracking strains. The reported method can predict initial and transverse cracks on quasi-isotropic laminates; further, it depicts the damage progress wherein microcrack nucleation and coalescence occurring before the full-width transverse cracking in laminated composites are observed under tensile loading conditions.